The silence of MUC2 mRNA induced by promoter hypermethylation associated with HBV in Hepatocellular Carcinoma - Ling Yang; Zhu Jing; Gao Lu; Liu Yongping; Zhu Changtai; Li Rong; Wei Lixin; Zhang Changsong (BMC, 2013)
Abstract Background To evaluate the promoter methylation status of MUC2 gene and mRNA expression in patients with hepatocellular carcinoma. Methods We analyzed MUC2 methylation by MSP, and MUC2 mRNA by real-time PCR in 74 HCC. Results MUC2 mRNA were lower in HCC tissues (Mean -ΔCt = −4.70) than that in Non-HCC tissues (Mean -ΔCt = −2.98). Expression of MUC2 was elevated in only 23 (31.08%) of the 74 HCC patients. MUC2 promoter was hypermethylated in 62.2% (46/74) of HCCs, and in only 18.9% (14/74) of non-tumor samples. MUC2 mRNA were lower in HCC patients with hypermethylation (Mean -ΔΔCt = −2.25) than those with demethylation (Mean -ΔΔCt = −0.22), and there is a decreased tendency for MUC2 mRNA in HCC patients with promoter hypermethylation (p = 0.011). There was a significantly correlation found between MUC2 mRNA and HBV and AFP in HCC. The loss of MUC2 mRNA and hypermethylation could be poor prognostic factors. After treated by 5-Aza-CdR and TSA, we found that MUC2 mRNA induced significantly in 7721, Huh7 and HepG2 cells. Conclusion The results suggested that MUC2 mRNA silenced by promoter hypermethylation is associated with high levels HBV in HCC.